Yanzhou Coal Mining Company Limited. Overseas acquisitions (A) - McFarlan, F. Warren (Franklin Warren); Jin, Yongjun; Li, Xiaohui ([London] : SAGE, 2016)
In October 2009, Zhang Baocai, a board member of Yanzhou Coal Mining Company Limited and a key acquisition negotiator, asked himself, "Will the acquisition of Felix Resources Limited be approved by the Foreign Investment Review Board? Do we need to do more for this?" Yanzhou Coal is controlled by Yankuang Group, a state-owned enterprise situated in Shandong Province. Yanzhou Coal is listed in Hong Kong, New York and Shanghai. The acquisition of Felix would be the second for Yanzhou Coal in Australia.
Originally Published in: McFarlan, F. W., Jin, Y. & Li, X. (2013). Yanzhou Coal Mining Company Limited: Overseas Acquisitions (A). 0-413-321. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Yanzhou Coal Mining Company Limited (Firm); Consolidation and merger of corporations -- China -- Case studies; Consolidation and merger of corporations -- Australia -- Case studies; International business enterprises -- Case studies